Clinical Characteristics, Management, and Outcomes of CLIPPERS:: A Comprehensive Systematic Review of 140 patients from 100 Studies - DelCimmuto, Nicholas R; Al-Chalabi, Mustafa; Beran, Azizullah; Devarasetty, Pratyush Pavan; Mhanna, Asmaa; Sheikh, Ajaz (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF To see the formatted meeting abstract.